Development of Google Sites-Based Teaching Materials With Doratoon In The Course of Aqidah And Morals on Praiseable Morals For Grade XI At MAN 2 Bojonegoro - Ahmad Muthi'Uddin; Sauqi Futaqi; Muhtadi Ridwan; Af’ydatul Maulia; Agus Moh. Sholahuddin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Teaching materials are very important for the teaching and learning process, with this teaching material it is hoped that the material to be provided by educators will be conveyed properly by students. Teaching materials have their own advantages, namely students can learn independently by using communication tools such as cellphones and computers so that they are more practical and can be accessed anytime and anywhere when needed. The purpose of researchers developing this teaching material is to find out the process of developing teaching materials based on Google Sites with Doratoon in the subject of aqidah akhlak material praiseworthy morals class XI MAN 2 Bojonegoro and to determine the feasibility of developing teaching materials based on Google Sites with Doratoon in the subject of aqidah akhlak material praiseworthy morals class The research method used is Research and Development (R&D) with the ADDIE model including analysis, design, development, implementation, evaluation. Data in development research are observations, interviews, questionnaires, and documentation. Assessment in Google Sites teaching materials with Doratoon includes media expert validation, material expert validation, product trials, student responses and educator responses related to learning teaching materials. The results of the assessment of the development of teaching materials on Google Sites with Doratoon include media expert validation with an average of 85% with a very feasible category, material expert validation with an average of 95.83% with very feasible, practicality of educators and students averaging 96.29% with a very feasible category and trials to students and educators with readability aspects got an average score of 92.92% with a very feasible category. So it is stated that the development of teaching materials based on Google Sites with Doratoon is very feasible to use in learning Aqidah Akhlak subject matter of commendable morals.